Unusually cruel : prisons, punishment, and the real American exceptionalism - e uthor (New York : Oxford University Press, 2017)
"The United States incarcerates far more people than any other country in the world, at rates nearly ten times higher than other liberal democracies. Indeed, while the U.S. is home to 5 percent of the world's population, it contains nearly 25 percent of its prisoners. But the extent of American cruelty goes beyond simply locking people up. At every stage of the criminal justice process - plea bargaining, sentencing, prison conditions, rehabilitation, parole, and societal reentry - the U.S. is harsher and more punitive than other comparable countries. [This book] argues that the American criminal justice and prison systems are exceptional - in a truly shameful way. Although other scholars have focused on the internal dynamics that have produced this massive carceral system, [the author] provides the first sustained comparative analysis that shows just how far the U.S. lies outside the norm of established democracies. And, by highlighting how other countries successfully apply less punitive and more productive policies, [the author] provides ... solutions to addressing America's criminal justice quagmire."--
Introduction -- Plea bargaining -- Sentencing -- Prison conditions -- Rehabilitation -- Parole -- Societal reentry -- Explaining American punitiveness : race, religion, politics, and business -- Conclusion.
Includes bibliographical references (pages 233-265) and index.
Keywords: Criminal justice, Administration of -- United States; Prisons -- United States; Corrections -- United States; Correctional law -- United States; Exceptionalism -- United States; POLITICAL SCIENCE -- American Government -- State & Provincial; POLITICAL SCIENCE -- Law Enforcement; SOCIAL SCIENCE -- Privacy & Surveillance; Correctional law; Corrections; Criminal justice, Administration of; Exceptionalism; Prisons; United States; USA; United States; 86.43 criminal procedure law, criminal law sanctions; 86.44 penitentiary law